Low back pain, influence of anxiety in its treatment - Ibrahimi-Kachuri D., &; Aleksovska Velichkovska L.; Shukova Stojmanovska D. (Faculty of physical education, sport and health, 2018)
Background: The low back pain is a huge problem nowadays, and it is experienced by a majority of the population during their whole life. Chronic low back pain is a state that is affected by biological, psychological and social factors that interfere among themselves and together affect each other, these factors influence increase and duration of complaining time. Material and Methods: The research was conducted in Physiotherapy Institute of Occupational Medicine (IOM) in Obiliq, Kosovo, during the period of one year, from January 2016 until the end of December 2016. The research was long-term and prospective. 63 patients participated in this research. All of them were treated with physical therapy, depending on examination and findings on patient. Results: Based on the obtained results, it can be concluded that the intensity of pain in patients before and after the treatment affects anxiety. Respectively, the patients who had high intensity pain also manifested higher level of anxiety. Conclusion: Anxiety influences the rehabilitation of low back pain, the patients who suffer from low back pain and have psychological problems such as anxiety, their level of pain prior and following the physiotherapy treatment remains without significant difference.
Keywords: Low Back Pain, Anxiety and Chronic Pain